2019
DOI: 10.3390/antiox8110506
|View full text |Cite
|
Sign up to set email alerts
|

Puffing as a Novel Process to Enhance the Antioxidant and Anti-Inflammatory Properties of Curcuma longa L. (Turmeric)

Abstract: Curcuma longa L. (turmeric) is used as a food spice; however, its strong taste restricts wider applications as a food ingredient despite its well-known health benefits. To develop an effective yet simple process for enhancing its antioxidant and anti-inflammatory activities, turmeric was gun-puffed at various pressures. Puffed turmeric exhibited an increase in its brown color and porous structures, indicating the occurrence of the Maillard reaction and vaporization during the process. Proximal analysis reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 31 publications
4
34
0
Order By: Relevance
“…As compared to LPS-induced upregulation of transcription of both genes, PTE but not TE suppressed the transcription of those genes ( Figure 3 ), confirming that increased OCR affects the suppressed inflammatory responses in macrophages. Together with the previous observations of reduced cytokine secretion (IL-6 and TNF-α) and surface marker expression (CD80 and CD86) [ 11 ], the current study clearly demonstrates that puffing increases the anti-inflammatory effects of turmeric.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…As compared to LPS-induced upregulation of transcription of both genes, PTE but not TE suppressed the transcription of those genes ( Figure 3 ), confirming that increased OCR affects the suppressed inflammatory responses in macrophages. Together with the previous observations of reduced cytokine secretion (IL-6 and TNF-α) and surface marker expression (CD80 and CD86) [ 11 ], the current study clearly demonstrates that puffing increases the anti-inflammatory effects of turmeric.…”
Section: Discussionsupporting
confidence: 88%
“…It was also reported that emulsion formation of curcumin with oils aid in the bioaccessibility through the lipid digestion and absorption system in the gastrointestinal tract [ 25 ]. In an extension to those studies, we previously reported that puffing, a simple processing method, successfully enhanced turmeric’s antioxidant and anti-inflammatory effects in vitro, although the detailed mechanisms are still unknown [ 11 ]. Puffing is a physical transformation that increases porosity and causes chemical reactions, including the well-defined Maillard reaction, the products of which have antioxidant capacities [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemically, curcumin is a bis-R,unsaturated-diketone commonly called diferuloylmethane [9]. Many studies showed that curcumin exhibits antimicrobial activity [10], anti-inflammatory ، antitumor and ant oxidative properties [11][12][13], and enhance liver enzyme [14]. Moreover, it has been indicated hypolipidemic effects of turmeric and curcumin [15,16].…”
Section: Introductionmentioning
confidence: 99%